1998
DOI: 10.1136/ip.4.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Trends in injury mortality among adolescents in Taiwan, 1965–94

Abstract: Objectives-To describe trends in injury mortality among adolescents in Taiwan for prioritising preventive interventions. Methods-Adolescent injury mortality data for Taiwan Conclusions-The increase in injury mortality rates among adolescents over the past three decades appears to be due largely to the increase in MVI mortality rates with males aged 15-19 years accounting for most of this increase. Priorities for adolescents in Taiwan are MVI (especially motorcyclists) and drownings. (Injury Prevention 1998;4:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Two studies reported variable rates19 28 and one rising rates 24. The study by Mujkic and colleagues28 reported on a period of conflict, and so is arguably atypical.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies reported variable rates19 28 and one rising rates 24. The study by Mujkic and colleagues28 reported on a period of conflict, and so is arguably atypical.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, mortality rates were also falling for specific types of injuries, where these were reported (particularly deaths from burns/fire, drowning and poisoning) (table 2). The notable exception was mortality from road traffic injury, where seven studies reported rising or variable road traffic injury mortality,19 23 24 30 35 40 41 particularly in older adolescents23 40 41 where this was specified. Greater variability in trends in injury mortality was seen in studies from the middle income countries compared with those from high income countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The burden of acute disease in sub-Saharan Africa is severely under-documented: Some data exist on the distribution of inpatient diagnoses in the region, but the actual range of acute presentations to health facilities is largely unknown (23,24,25) . 2.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%